The dependence of Net-Radiation on Short-Wave Radiation at Waltair (MAUSAM, 1967)
The constants of the general radiation balance equation suggested by Monteith and Szeicz (1961) are redetermined for the tropical latitude station, waltair. The calculated radiation balance equation with new constants for the station is R=0.86(1-a) S-4.2. A high correlation coefficient 0.99 is obtained between net short wave radiation (1- a) S and net radiation R.